(untitled) (Global Journal of Human-Social Science, 2018)
This study investigated the effects of Mobile Learning on students academic performance and student attitudes about the use of mobile devices for learning The study used the quasi-experimental approach Respondents in this study consisted of 42 Adeyemi College of education social studies English language major that were on teaching practice at National Institute for Educational Planning and Administration Ondo The students were divided into experimental and control groups of 21 students in each The soft copy of the course content on Strategies of Teaching and Learning was uploaded to the mobile phone for students in the experimental group Another hardcopy of the course content was delivered to students in the control group by hand in the first meeting Data collection tools included an academic performance examination and students attitudinal questions The result was analyzed using Relative Importance Index Simple percentage Analysis of Variance and Independent Sample t Test It was found that mobile learning had quite significant effect on students academic performance and student attitudes about using mobile phone for learning were moderately positive with a pooled RII of 89 48 on a likert scale of 1 Not at all well to 5 Extremely well In view of these it was recommended that educationists as well as educational institutions to take the next step in effectively integrating mobile devices and instruction optimized for mobile devices in education in order to improve teaching and learning